If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6y + -24 = 48 Reorder the terms: -24 + 12x + -6y = 48 Solving -24 + 12x + -6y = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 12x + 24 + -6y = 48 + 24 Reorder the terms: -24 + 24 + 12x + -6y = 48 + 24 Combine like terms: -24 + 24 = 0 0 + 12x + -6y = 48 + 24 12x + -6y = 48 + 24 Combine like terms: 48 + 24 = 72 12x + -6y = 72 Add '6y' to each side of the equation. 12x + -6y + 6y = 72 + 6y Combine like terms: -6y + 6y = 0 12x + 0 = 72 + 6y 12x = 72 + 6y Divide each side by '12'. x = 6 + 0.5y Simplifying x = 6 + 0.5y
| -5(10+x)=10 | | -(5-2x)+x=7(x-2) | | -25x+5y=30 | | N-1.5=12.6 | | 3.8q-3.5-4.7q=1.9q-5.9 | | 3x(2x+6b)= | | 16=8x-4y | | 47-7x=11x+23 | | 6x-7-2x=21-3x | | N+85=180 | | 3(-x-4)=2x+3(x-5) | | -y=-4(-2)+8 | | 3(x+2)+7=5(x+1)+2 | | N-21/2=71/2 | | y=x^2-10x+27 | | -y=-4(0)+8 | | 1/7(x+21)-1/8(x-8)=x+7 | | -y=-4(2)+8 | | 5x+11=49 | | -15+5(-2)=-5y | | 3x(3x+2)=3x-4 | | -15+5(0)=-5y | | 9x+25=43 | | -15+5(2)=-5y | | -2(2x-6)=32 | | 6x^2=x-24 | | 7x-10+x+4=90 | | -4=(-2) | | -4=(0) | | 7x-10+x+4=180 | | 24x-3y-18=0 | | -2=(2) |